Perbandingan Efektivitas BAE dengan Senam Kaki Terhadap Sirkulasi Darah Perifer dan Kadar Glukosa Darah pada Penderita Diabetes Melitus Tipe 2 - Saleha Salihun; Irfan Idris; Andi Ariyandy (Jurnal Kesehatan, 2022)
This study compared the..effectiveness..of..Buerger..Allen..exercise with foot exercise on peripheral blood circulation and..fasting..blood..glucose..levels..in..patients with..Type 2 Diabetes Mellitus. This comparative analytical research uses a pretest-posttest design of 2 groups in pairs. Thirty-two patients..with..Type..2 Diabetes..Mellitus..were..divided..into two groups, consisting of 16 people. The first and second groups were treated with the Buerger..Allen..and foot..exercises, respectively. The..Ankle..Brachial test for assessing peripheral blood circulation index (ABI) and blood glucose levels (GDP and 2 hours..Post..Pradinal) ..were measured pre treatment and after 24 treatments for eight weeks. The results based..on..the..Paired..t-test analysis showed that there was an increase..in the..ABI value and a decrease in fasting..blood..glucose.. (GDP) levels, and 2 hours Post Prandial (PP) in the treatment..group..that was given the Buerger Allen exercise and the treatment group who was given leg exercises (p). =0.001). Furthermore, from the Independent t-test, it was found that the Buerger Allen exercise had a difference in the increase in ABI values ​​that were higher than the foot exercise(p=0.001). However, the difference was the highest decrease with a decrease in fasting blood glucose (GDP) and 2 hours PP). namely in the foot exercise group (p = 0.004 and p = 0.037). This study concludes that the Buerger..Allen..exercise..is more effective than leg gymnastics to increase the ABI value. In contrast, foot exercise is more effective than the Buerger..Allen..exercise in reducing blood glucose levels